Tinjauan Arsitektur Rumah Adat Batak Toba di Pulau Samosir - Sukawati Susetyo (Berkala Arkeologi Sangkhakala, 2009)
AbstractMany of Batak Toba traditional houses are still found in Pulau Samosir, and other areas in North Sumatra. When studying the techniques of this traditional house structure design, we have great admiration for the creativity our ancestors. All materials come from the natural environment where they lives, as well as building technique have been taking into account the various effects caused by the earthquake and fire has been well anticipated. Beside that, all the elements of building and decorative art which have been drawn by high philosophical meaning. As technology development, the building materials